Searching for Data: Nature and Flow of Information Underlying Urban Wild Boar Management Policies. Bordeaux (France) as a Case Study - Carole Marin; Paul Bellalba (Cybergeo)
Nature in the city harbours a wide range of biodiversity. While some species are welcomed, others have settled in uninvited. This is the case with wild boar. The challenge of managing large urban wildlife is not only ecological but also cultural, political, and ethical. This study, driven by the general uncertainty surrounding the socio-ecological issues of coexistence with urban wild boar and potential solutions, explores and discusses the nature and flow of information underlying the specie’s management policies. Our approach is based on a field survey conducted in Bordeaux Metropolis, aimed at tracking the shared information between local stakeholders. The objectives are twofold: i) to gather and analyse existing data on urban wild boar, the problems generated by their presence in the city, and the management systems; ii) to model information flows between social groups facing the challenges of coexistence with wild boar or involved in their management. The study points to a lack of data, along with a general confusion regarding key organisations responsible for monitoring and managing the issue. While the effectiveness of management policies depends on the ability to frame the problem, data is used as an instrument of power by actors engaged in social legitimacy struggles. Assuming that the integration of information is a prerequisite for freedom in urban wildlife management choices, we discuss the implementation of a collaborative reporting platform, tailored to the urban socio-ecological context.Keywords: fauna, city, management, conflict, knowledge, social network